2016
DOI: 10.1108/jsma-06-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

Increasing customer loyalty and customer intimacy by improving the behavior of employees

Abstract: Purpose One of the most important characteristics of high-performance organizations is that these organizations always aim at servicing their customers as best as possible. In practice, this means that the employees of these organizations have to behave toward customers in such a way that these customers are not only fully satisfied but also become loyal to the organization. The purpose of this paper is to look at the concrete behaviors that are needed to create this customer loyalty. Design/methodology/appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 40 publications
(84 reference statements)
2
43
2
Order By: Relevance
“…They argue that for organizations to achieve their objectives, employees have to understand the importance of the customer to the organization since the organization ceases to exist if there are no customers. They identified behavioural factors such as (service quality (SQLTY), need understanding (NEEDUND), as some of the factors if display by employees towards customers could possibly lead to intimacy (INTIMACY) and subsequently lead to customer loyalty (for more commentary on this, see de Waal et al, 2016). In this study, the customer (herein refer to student) loyalty will be used and for more similar work (see, Helgesen & Nesset, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…They argue that for organizations to achieve their objectives, employees have to understand the importance of the customer to the organization since the organization ceases to exist if there are no customers. They identified behavioural factors such as (service quality (SQLTY), need understanding (NEEDUND), as some of the factors if display by employees towards customers could possibly lead to intimacy (INTIMACY) and subsequently lead to customer loyalty (for more commentary on this, see de Waal et al, 2016). In this study, the customer (herein refer to student) loyalty will be used and for more similar work (see, Helgesen & Nesset, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Past researchers have identified intimacy as playing an important role and a dual one between the customer and the organization relationship building process (Treacy & Wiersma,1993). As cited in de Waal et al (2016), customer intimacy is defined as "making customers feel good whenever they make contact with your company" (Ballou, 2006, p. 5, cited in IBM Global Services, 2006 or "tailoring and shaping products and services to fit the increasingly specific definition of the customer" (Bügel, 2010, p. 65). Empirically, past researchers ( for more details see, Fleming et al, 2005;Lloyd & Luk, 2011;Pitta et al, 2006, Lau, 2000Xu & Van der Heijden, 2005;Yim et al, 2008) observed that having a good interaction with customers and employees of an organisation impact on customer intimacy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations